Features of the respiratory function in children with community-acquired pneumonia - D.V. Usenko (Zaslavsky O.Yu., 2019)
Background. New opportunities for improving the respiratory function are associated with the use of high-frequency chest wall oscillation, which allows us to restore the drainage function of the bronchial tree and optimize pulmonary ventilation. The purpose was to study and estimate the respiratory function in children with community-acquired pneumonia. Materials and methods. The study involved 107 children (the main group - 55 persons and the control group - 52 persons) aged 6-17 years with acute and uncomplicated community-acquired pneumonia. Children of the main group received basic therapy with high-frequency chest wall oscillation, while patients of the control group received only basic therapy. The evaluation of respiratory function was performed in the dynamics of treatment using spirometry. Results. At the beginning of therapy for community-acquired pneumonia, the respiratory function indices in the studied groups had insignificant differences. Consequently, analysis of respiratory function parameters in children of the main group on the 10th day of basic therapy has shown the improvement of forced expiratory volume in 1 second (FEV1) (88.36 ± 1.55 %, p = 0.02), vital capacity (VC) (88.18 ± 1.53 %, p = 0.02), forced vital capacity (FVC) (86.77 ± 1.37 %, p = 0.03), maximal expiratory flow at 25 % of FVC (MEF25) (90.10 ± 2.99 %, p = 0.02) and maximal voluntary ventilation (MVV) (88.31 ± 1.70 %, p = 0.04). Moreover, when comparing indicators of the respiratory function in the control group children, a less pronounced dynamics was noted, in particular FEV1 (81.65 ± 2.44 %, p = 0.02), VC (82.95 ± 2.56, p = 0.02), FVC (80.85 ± 2.09, p = 0.03), MEF25 (82.63 ± 3.08 %, p = 0.02) and also MVV (85.65 ± 1.99 %, p = 0.04). As a result of the receiver operating characteristic (ROC) analysis, the dynamics of the respiratory function restoration in the main group children is more significant due to the improvement in MVV, as evidenced by the large area under the ROC curve (AUC) - 0.99, FEV1 - AUC 0.94 and FEV1/FVC - AUC 0.94. In control group children, the dynamics of the studied parameters of the respiratory function was less pronounced, which is confirmed by the MVV - AUC 0.63, FEV1 - AUC 0.79 and FEV1/FVC - AUC 0.89. Conclusions. To improve the ventilation function of the lungs in children with community-acquired pneumonia, it is necessary to carry out bronchial drainage procedures using high-frequency chest wall oscillation as a part of basic therapy, as evidenced by the positive results obtained from spirometry.